Transmission of a pathogenic virus (Iridoviridae) of Culex pipiens larvae mediated by the mermithid Strelkovimermis spiculatus (Nematoda) - Muttis, Evangelina (2015)
Little progress been made in elucidating the transmission pathway of the invertebrate iridescent virus (MIV). It has been proposed that the MIV has no active means to enter the mosquito larva. We have previously found that the presence of the mermithid nematode Strelkovimermis spiculatus is associated with MIV infection in Culex pipiens under field conditions. In the present study, we evaluated the transmission of MIV to C. pipiens larvae mediated by S. spiculatus and several factors involved in this pathway (mosquito instars, nematode:mosquito larva ratio, amount of viral inoculum). Our results indicate that S. spiculatus functions as an MIV vector to C. pipiens larvae and seems to be an important pathway of virus entry into this system. Moreover, TEM images of S. spiculatus exposed to the viral suspension showed no infections inside the nematode but showed that viral particles are carried over the cuticle of this mermithid. This explains the correspondence between MIV infection and the factors that affect the parasitism of S. spiculatus in C. pipiens larvae.